Editorial: The marine iodine cycle, past, present and future - Rosie Chance; Gregory A. Cutter; Dalton S. Hardisty; Anoop S. Mahajan (Frontiers in Marine Science, 2024)

Hydrothermal Activity and Seismicity at Teahitia Seamount: Reactivation of the Society Islands Hotspot? - Christopher R. German; Joseph A. Resing; Guangyu Xu; Isobel A. Yeo; Sharon L. Walker; Colin W. Devey; James W. Moffett; Gregory A. Cutter; Olivier Hyvernaud; Dominique Reymond (Frontiers in Marine Science, 2020)

Elevated trace metal content of prokaryotic communities associated with marine oxygen deficient zones - Daniel C. Ohnemus; Sara Rauschenberg; Gregory A. Cutter; Jessica N. Fitzsimmons; Robert M. Sherrell; Benjamin S. Twining (Limnology and Oceanography, 2017)
Little is known about the trace metal content of marine prokaryotes, in part due to their co‐occurrence with more abundant particulate phases in the upper ocean, such as phytoplankton and biogenic detritus, lithogenic minerals, and authigenic Mn and Fe oxyhydroxides. We attempt to isolate these biomass signals in particulate data from the US GEOTRACES Eastern Pacific Zonal Transect (cruise GP16) in the Eastern Tropical South Pacific (ETSP), which exhibited consistent maxima in P and other bioactive trace metals, and minima in particulate Mn, in the oxygen deficient zones (ODZs) of 13 stations. Nitrite maxima and nitrate deficits indicated the presence of denitrifying prokaryotic biomass within ETSP ODZs, and deep secondary fluorescence maxima at the upper ODZ boundaries of 10 stations also suggested the presence of low‐light, autotrophic communities. ODZs were observed as far west as 99°W, more than 2300 km from the South American coast, where eolian lithogenic and lateral/resuspended sedimentary inputs were negligible, presenting a unique opportunity to examine prokaryotic metal stoichiometries. ODZ particulate P maxima can rival gyre mixed layer biomass concentrations, are highly sensitive to oxygen, and are in excess of amounts scavengable by local Fe oxyhydroxides and acid–volatile sulfides. Even after correction for lithogenic and ferruginous–scavenged metals, ODZ P‐maxima are often enriched in Cd, Co, Cu, Ni, V, and Zn, exhibiting particulate trace metal ratios to P that exceed mixed layer biomass ratios by factors of 2–9. ODZ prokaryotic communities may be largely hidden, TM–rich pools involved in the marine cycles of these bioactive trace metals.

Arsenic and phosphorus biogeochemistry in the ocean: Arsenic species as proxies for P‐limitation - Oliver Wurl; Louise Zimmer; Gregory A. Cutter (Limnology and Oceanography, 2013)
Arsenic and phosphorus are biochemically very similar, and hence arsenate (As 5+ ) is toxic by interfering with the energy metabolism, in particular during P limitation. However, many phytoplankton detoxify As by reducing arsenate to arsenite (As 3+ ), and/or methylating it to mono and dimethyl As. Such As detoxification becomes operative in oligotrophic waters when phosphate concentrations are below those for As; therefore, we evaluated the potential use of these detoxification products as indicators of P limitation by measuring As speciation during the US GEOTRACES North Atlantic transect. The distribution of As 3+ concentrations in surface waters is similar to that of N : P ratios and alkaline phosphatase activity (APA), two conventional proxies for P‐limitation. As 3+ concentrations have a very similar relationship to phosphate as APA to phosphate, and therefore indicate the potential of As 3+ as proxy for P‐limitation. From the relationship to phosphate we derived threshold valuesof As 3+ concentration to indicate moderate and extreme P‐limitation. We then applied these threshold values to assess P‐limitation with high horizontal resolution in the North Atlantic, improving on the contradictory assessments using the conventional proxies. Our new evaluation is consistent with the general concept that the North Atlantic is moderately to extremely limited in phosphate.

Sources and cycling of carbonyl sulfide in the Sargasso Sea - Gregory A. Cutter; Lynda S. Cutter; Katherine C. Filippino (Limnology and Oceanography, 2004)
The cycling of the radiatively important gas carbonyl sulfide (OCS) was studied in surface waters of the Sargasso Sea. In August 1999, surface OCS concentrations averaged 8.6 pmol L −1 , showed minor diel variations, and varied little with depth. An OCS precursor, total dissolved organic sulfur (DOS), was lowest at the surface (40 nmol L −1 ) and increased with depth. The photoproduction rate of OCS from in situ incubations averaged 9.6 pmol L −1 h −1 , whereas dark production was 7.0 pmol L −1 h −1 . Apparent quantum yields were 10 −5 −10 −7 from 313–436 nm and varied with the water depth irradiated. In March 2000, there were strong diel variations in surface OCS (highest in late afternoon; overall average, 16.9 pmol L −1 ). Depth profiles in the afternoon showed surface water maxima and decreases with depth, whereas DOS had a surface maximum of 419 nmol L −1 and decreased with depth. Dark production was 4.0 pmol L −1 h −1 . Modeling of the diel cycle suggested a photoproduction rate of 16.4 pmol L −1 h −1 . Overall, the photochemical production of OCS strongly depended on DOS and chromophoric dissolved organic matter, whereas dark production was influenced by the presence of particles and perhaps microbial respiration, showing a direct biotic influence on OCS cycling.

Light dependence of selenium uptake by phytoplankton and implications for predicting selenium incorporation into food webs - Stephen B. Baines; Nicholas S. Fisher; Martina A. Doblin,; Gregory A. Cutter,; Lynda S. Cutter; Brian Cole (Limnology and Oceanography, 2004)
The potentially toxic element selenium is first concentrated from solution to a large but highly variable degree by algae and bacteria before being passed on to consumers. The large loads of abiotic and detrital suspended particles often present in rivers and estuaries may obscure spatial and temporal patterns in Se concentrations at the base of the food web. We used radiotracers to estimate uptake of both selenite (Se(IV)) and C by intact plankton communities at two sites in the Sacramento/San Joaquin River Delta. Our goals were to determine (1) whether C and Se(IV) uptake were coupled, (2) the role of bacteria in Se(IV) uptake, and (3) the Se :C uptake ratio of newly produced organic material. Se(IV) uptake, like C uptake, was strongly related to irradiance. The shapes of both relationships were very similar except that at least 42–56% of Se(IV) uptake occurred in the dark, whereas C uptake in the dark was negligible. Of this dark Se(IV) uptake, 34–67% occurred in the 0.2–1.0‐ µm size fraction, indicating significant uptake by bacteria. In addition to dark uptake, total Se(IV) uptake consisted of a light‐driven component that was in fixed proportion to C uptake. Our estimates of daily areal Se(IV) :C uptake ratios agreed very well with particulate Se :C measured at a site dominated by phytoplankton biomass. Estimates of bacterial Se :C were 2.4–13 times higher than for the phytoplankton, suggesting that bacteriovores may be exposed to higher dietary Se concentrations than herbivores.

Uptake of dissolved organic selenides by marine phytoplankton - Stephen B. Baines; Nicholas S. Fisher; Martina A. Doblin; Gregory A. Cutter (Limnology and Oceanography, 2001)
Se is present in multiple oxidation states in nature, each of which has unique chemical and biological reactivities. As a consequence, the rate of Se incorporation into food webs or its role as either a limiting nutrient or a toxic substance is a function of complex biogeochemistry. In particular, little is understood about the accumulation of dissolved organic selenides by phyto‐ or bacterioplankton. We assessed the bioavailability of dissolved organic selenides to marine and estuarine phytoplankton by presenting various algal species with filtered lysates of the diatom, Thalassiosira pseudonana, grown on media amended with radiolabeled selenite ( 75 Se[IV]). Species known to accumulate selenite effectively also accumulated Se from radiolabeled cell lysates and to approximately the same extent. When exposed to a 4.5‐nM solution of lysate Se, T. pseudonana , Heterocapsa triquetra (Dinophyceae), Tetraselmis levis (Prasinophyceae), Synechococcus bacillus (Cyanobacteria), and Dunaliella tertiolecta (Chlorophyceae) incorporated 42%–53%, 42%, 30%, 32%, and 4% of the dissolved Se, respectively. Se cell contents of T. pseudonana, T. levis, and D. tertiolecta grown in media containing 4.5 nM lysate Se were very similar to Se content of cells grown in 4.5 nM selenite. Our results suggest that recycling of Se(—II) may be more important than previously thought. Consequently, uptake of organic selenides by phytoplankton may need to be considered in models predicting Se incorporation into aquatic food webs, given that it is a significant fraction of dissolved Se in estuarine and oceanic waters.